DAMPAK KENAIKAN TARIF PPN TERHADAP TINGKAT KEMISKINAN DI INDONESIA - Kadek Lia Fitriani; Febsri Susanti (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Poverty remains a serious issue in Indonesia, and since the implementation of the 11% VAT policy in April 2022, public concerns about its impact on livelihoods, particularly among the lower-middle class, have increased. Therefore, this study aims to address these concerns by examining the impact of the VAT rate increase on poverty levels in Indonesia. This research employs a qualitative literature study method using secondary data, including publications from the Statistics Indonesia (BPS), scientific journals, e-books, and online news. Data analysis was conducted using the Miles and Huberman approach, which involves data reduction, data presentation, conclusion drawing, and verification. The findings indicate that the increase in the VAT rate to 11% does not directly lead to a rise in poverty levels. In fact, it provides benefits such as increased tax revenue, which is expected to reduce the national budget deficit and promote development. However, this policy also impacts the public's purchasing power, leading to a decrease in consumption. The government is expected to continue monitoring and strengthening mitigation policies to address the impact of the VAT rate increase, preventing misuse and inefficiency in the budget.